Increased Noradrenaline as an Additional Cerebrospinal Fluid Biomarker in PSP-Like Parkinsonism - Cerroni, Rocco; Liguori, Claudio; Stefani, Alessandro; Conti, Matteo; Garasto, Elena; Pierantozzi, Mariangela; Mercuri, Nicola B.; Bernardini, Sergio; Fucci, Giorgio; Massoud, Renato (Frontiers in Aging Neuroscience, 2020)
Academic centers utilize sequential clinical and neuroimaging assessments, including morphometric ratios, to obtain an unequivocal diagnosis of the non-synucleinopathic forms of Parkinsonism, such as progressive supranuclear palsy (PSP); however, a 1–2 year follow-up is required. Hence, the on-going long-lasting trials using anti-tau antibodies for PSP patients might be biased by the incorrect enrollment of Parkinson’s disease (PD) patients manifesting early axial signes. This perspective study obeyed to two mayor goals; at first, to summarize the established biomarker candidates found in cerebrospinal fluid (CSF) in probable PSP patients, including low p-tau and altered neurofilaments. In addition, we show our recent data, from CSF samples from well-selected PSP subjects attributable to both main variants (and revisited in light of MDS criteria) that were followed for 1 year before and 2 years after lumbar puncture. We found a significantly high level of noradrenaline (NE) in these patients, similar to controls, when compared to PD ones. In contrast, CSF samples, in PD, showed a significant reduction in CSF NE and its major metabolite, which confirmed that PD is a multi-system disease involving several endogenous pathways. The NE axis impairments was prominent in PSP featuring worse NPI; it might represent a counterpart to the early and peculiar psycho-pathological profiles that are observed in taupathies. In conclusion, we highlight that CSF biomarkers, easy to collect, can provide rapid insights as diagnostic tools. Early alterations in endogenous NE machinery in atypical Parkinsonism may represent a specific risk trait in forms characterized by worse prognosis.